Acidification effects on biofouling communities: winners and losers. (28th January 2015) - Peck, Lloyd S.; Clark, Melody S.; Power, Deborah; Reis, João; Batista, Frederico M.; Harper, Elizabeth M.
Abstract: How ocean acidification affects marine life is a major concern for science and society. However, its impacts on encrusting biofouling communities, that are both the initial colonizers of hard substrata and of great economic importance, are almost unknown. We showed that community composition changed significantly, from 92% spirorbids, 3% ascidians and 4% sponges initially to 47% spirorbids, 23% ascidians and 29% sponges after 100 days in acidified conditions (pH 7.7). In low pH, numbers of the spirorbid Neodexiospira pseudocorrugata were reduced ×5 compared to controls. The two ascidians present behaved differently with Aplidium sp. decreasing ×10 in pH 7.7, whereas Molgula sp. numbers were ×4 higher in low pH than controls. Calcareous sponge ( Leucosolenia sp.) numbers increased ×2.5 in pH 7.7 over controls. The diatom and filamentous algal community was also more poorly developed in the low pH treatments compared to controls. Colonization of new surfaces likewise showed large decreases in spirorbid numbers, but numbers of sponges and Molgula sp. increased. Spirorbid losses appeared due to both recruitment failure and loss of existing tubes. Spirorbid tubes are comprised of a loose prismatic fabric of calcite crystals. Loss of tube materials appeared due to changes in the binding matrix and not crystal dissolution, as SEM analyses showed crystal surfaces were not pitted or dissolved in low pH conditions. Biofouling communities face dramatic future changes with reductions in groups with hard exposed exoskeletons and domination by soft‐bodied ascidians and sponges.